The Effect of Body Mass Index on Five Years Progression Free Survival in Breast Cancer - Wiwiek Probowati; Tejo Jayadi; brenda miriane rustam; agatha maheswari adita putri (Faculty of Medicine Universitas Kristen Duta Wacana, 2022)
Backgroud Breast cancer is the type of cancer that has the highest prevalence. Breast cancer growth is related to nutritional status. Nutritional status is assessed based on measurements of BMI Body Mass Index (BMI) and obesity is a factor that plays a role in the growth of cancer cells.Objective To investigate the effect of BMI on the five-year progression-free survival (PFS) of breast cancer patientsMethods A retrospective cohort study using observational methods on 82 female patients with breast cancer at Bethesda Hospital, Yogyakarta.Results A total of 82 medical records of breast cancer patients were collected at Bethesda Hospital Yogyakarta. A total of 71 patients (86.6%) were still alive, while 11 have died. This study found an average progression-free survival of BMI category <25 kg/m2 78,5 months while the BMI ≥ 25.0 kg/m² 80,9 months (HR 2,057, 95% CI: .457–2.491). In addition, BMI and other prognostic variables did not have a significant relationship with progression-free survival in breast cancer patients (p = 0.114).Conclusion In this study, Body Mass Index was not associated with the 5-year progression-free survival of breast cancer patients.